An updated advancement of bifunctional IL-27 in inflammatory autoimmune diseases - Xu, Wang-Dong; Wang, Da-Cheng; Zhao, Ming; Huang, An-Fang (Frontiers in Immunology, 2024)
Interleukin-27 (IL-27) is a member of IL-12 family. The gene encoding IL-27 is located at chromosome 16p11. IL-27 is considered as a heterodimeric cytokine, which is consisted of Epstein-Barr virus (EBV)-induced gene 3 (Ebi3), IL-27p28. According to function of IL-27, it binds to receptor IL-27rɑ or gp130, and then regulates downstream cascade. To date, findings showed that expression of IL-27 was abnormal in different inflammatory autoimmune diseases (including systemic lupus erythematosus, rheumatoid arthritis, sjogren syndrome, Behcet's disease, inflammatory bowel disease, multiple sclerosis, systemic sclerosis, type 1 diabetes, Vogt-Koyanagi-Harada, ankylosing spondylitis). Moreover, in vivo and in vitro studies demonstrated that IL-27 is significantly involved in the development of these diseases by regulating innate and adaptive immune responses, either playing an anti-inflammatory or pro-inflammatory role. In this review, we comprehensively summarized information about IL-27 and autoimmunity based on available evidence. Hopefully targeting IL-27 will hold great promise in treatment of inflammatory autoimmune disorders in the future.